Analisis Pengungkapan Corporate Social Responsibility PT. Bukit Asam, Tbk Berdasarkan Global Reporting Initiatives (GRI) Dan Kaitannya Dengan PROPER - Atika Tri Ningsih; Charoline Cheisviyanny (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to analyze: 1) The level of corporate social responsibility disclosure of PT. Bukit Asam, Tbk for the year 2017 and 2018 based on the GRI G4, 2) The similarity of each indicator contained in GRI G4 with PROPER which are issued by The Ministry of Environment. This is a descriptive qualitative research. The sample in this study was a mining company that revealed the sustainability report in 2017 and 2018 based on the GRI G4 standard and obtained a gold PROPER, namely PT. Bukit Asam, Tbk. The type of data were documentary data with secondary data sources and the analysis method were content analysis. The result show that: 1) Based on the results of content analysis on the level of disclosure of economic, environmental and social indicator on the sustainability report of PT. Bukit Asam, Tbk in 2017 is higher than in 2018 and the level of breadth and depth of the sustainability report of PT. Bukit Asam, Tbk in 2018 has a better category score than in 2017, 2) There are similarities GRI G4 indicator in environmental category as PROPER indicator items, namely energy, cesspool, water and biodiversity